2016
DOI: 10.3389/fchem.2016.00019
|View full text |Cite
|
Sign up to set email alerts
|

Base-Modified Nucleosides: Etheno Derivatives

Abstract: This review presents synthesis and chemistry of nucleoside analogs, possessing an additional fused, heterocyclic ring of the “etheno” type, such as 1,N6-ethenoadenosine, 1,N4-ethenocytidine, 1,N2-ethenoguanosine, and other related derivatives. Formation of ethenonucleosides, in the presence of α-halocarbonyl reagents and their mechanism, stability, and degradation, reactions of substitution and transglycosylation, as well as their application in the nucleoside synthesis, have been described. Some of the discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…The uracil base cannot be derivatized by CAA . However, the fluorescence produced by ϵ‐cytosine is too weak to be used for quantification . Therefore, the excitation‐emission spectra of ϵ‐adenine and ϵ‐guanine were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The uracil base cannot be derivatized by CAA . However, the fluorescence produced by ϵ‐cytosine is too weak to be used for quantification . Therefore, the excitation‐emission spectra of ϵ‐adenine and ϵ‐guanine were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that 2-aminopurine easily reacts with aqueous chloroacetaldehyde to give two fluorescent, isomeric products 1 and 2. Both products are substrates for the bacterial (E. coli) purine nucleoside phosphorylase, but in both cases the ribosylation site has been found to be N 2 rather than N 9 . The new ribosides are fluorescent and potentially useful as fluorescent probes.…”
Section: Discussionmentioning
confidence: 99%
“…Tri-cyclic nucleosides and nucleotides are also utilized as dimensional probes for enzymatic studies [5,6]. Some of the tri-cyclic analogs and their derivatives reveal promising anti-viral properties [7], recently reviewed by Janz-Wechmann et al [8,9]. They are known to reveal substrate or inhibitory activities towards many enzymes of purine metabolism [2], and they are important intermediates in the process of chemical mutagenesis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the same period, the synthesis of novel nucleoside analogues compounds were published, using guanosine as precursor [75]. First, halogen atom was incorporated at the 2-position of this base purine.…”
Section: Methods Of Synthesis Of Adenosine Derivatives Interaction Wmentioning
confidence: 99%